Aula extendida: acercando el aula universitaria a los contextos escolares para reducir la distancia “teoría-práctica" (Extended classroom: bringing the university classroom closer to the school context in order to reduce the distance between theory and pr - García-Monge, Alfonso; González-Calvo, Gustavo; Martínez-Álvarez, Lucio; Rodríguez-Campazas, Hugo (Retos, 2020)
Se evalúa una experiencia de “Aula Extendida” en la que se posibilita que estudiantes de la materia Educación Física Escolar del Grado en Educación Primaria acudan a un colegio a observar prácticas de Educación Física con escolares impartidas por sus docentes universitarios, participando en los procesos de diseño, observación y análisis-reformulación del proceso de enseñanza. La experiencia es altamente valorada por las personas participantes que, entre otras cosas, reconocen que les ayuda a ver detalles sobre la labor docente, a dar sentido al contenido teórico de otras materias del Grado y a cambiar su visión sobre la Educación Física.Abstract: We analyzed an experience on “extended classroom”, through which students enrolled in the course of Physical Education from the bachelor in Primary Education were allowed to attend Physical Education practices with schoolchildren taught by their university professors, as well as to participate in the processes of design, observation, and analysis-reformulation of the teaching process. The experience was highly valued by the participants, who, among other things, recognized that it helped them notice details about the teaching work, give meaning to theoretical contents of other bachelor courses, and change their vision about Physical Education.